2001
DOI: 10.1016/s1251-8050(01)01512-9
|View full text |Cite
|
Sign up to set email alerts
|

Réflexion sur le processus coracoı̈de des hominoı̈des et des atèles ; application à quelques hominidés fossiles

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Two radio-clinical studies in humans reported in 2006 [24,25] and 2013 [19] established that a large lateral extension of the acromion was among the bone morphology factors associated with rotator cuff tears. Although scapular anatomy and morphology has been the focus of a large number of studies in hominoids (gibbons, orang-utans, gorillas, chimpanzees, and humans) since the nineteenth century [1][2][3][4][5][6][7][8][9][10], very few of them involved comparisons of acromial process, coracoid process, or coraco-acromial arch morphology across hominoid species [12,21,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two radio-clinical studies in humans reported in 2006 [24,25] and 2013 [19] established that a large lateral extension of the acromion was among the bone morphology factors associated with rotator cuff tears. Although scapular anatomy and morphology has been the focus of a large number of studies in hominoids (gibbons, orang-utans, gorillas, chimpanzees, and humans) since the nineteenth century [1][2][3][4][5][6][7][8][9][10], very few of them involved comparisons of acromial process, coracoid process, or coraco-acromial arch morphology across hominoid species [12,21,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…2), in whom the glenoid cavity faces laterally. This orientation is used as a criterion to determine whether a scapula fragment is associated with tree-climbing behaviour [12,14,[28][29][30][31]. Given the lateral orientation of the human glenoid cavity, the axis of the scapula and that of the upper limb are not aligned until a considerable degree of flexion is achieved [32] (Fig.…”
Section: Discussionmentioning
confidence: 99%